Amino-Functionalization of Multiwall Carbon Nanotubes and Its Use for Solid Phase Extraction of Mercury Ions from Fish Sample. (20th June 2013) - Soleimani, Majid; Ghahraman Afshar, Majid; Sedghi, Arman
Abstract : We describe here the amino-functionalization of multiwall carbon nanotubes (MWCNTs) and also its application as an adsorbent of solid phase extraction (SPE). The amino-functionalized MWCNTs have a good capacity to retain Hg 2+, but the raw and purified MWCNTs are found not to adsorb Hg 2+ ions. The amino-functionalized MWCNTs are prepared with amino-functionalization of purified MWCNTs by ethylenediamine. The physicochemical properties of purified and amino-functionalized MWCNTs are characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, and the Boehm titration. The amino-functionalized MWCNTs are selected as novel sorbents for the solid phase extraction of Hg 2+ . The amino-functionalized MWCNT-SPE method is used for the determination of Hg 2+ from complex matrix including fish and real water samples. Effective parameters on Hg 2+ retention such as pH, flowrate, nature of the eluent, the ionic strength, selectivity coefficient, and retention capacity are investigated. The enrichment factor and maximum capacity of the sorbent are 100 mL and 11.58 mg/g, respectively. The linear range, limit of detection, and relative standard deviation of the proposed method are 0.003 to 0.3 μ g/L, 1.25 × 10 − 3 μ g/L, and 2.23%, respectively. Selectivity experiments show that the adsorbents have a stronger specific retention for Hg 2+ than Fe 3+, Cu 2+, Pb 2+, Ni 2+, Mn 2+, Ca 2+, and Mg 2+ .